Factors Influencing Small and Medium Enterprise Performance in Nigeria: A Pilot Study - Ibrahim, Maryam Imam; Ooi, Yeng Keat; Abdul Rani, Shamsul Huda (UUM Press, 2018)
This paper discusses factors influencing the performance of SMEs in Nigeria using the quantitative approach. The study used a survey method; it administered 40 questionnaires to SME owner-managers randomly selected in Kano, Nigeria. Four elements were identified and used as determining factors of SMEs performance, these are: entrepreneurial orientation, technology orientation and contemporary marketing as independent variables and government support policies (GSPs) as a moderating variable. Validity and reliabilty of the instruments were scrutinized by professionals in the field of management and their observations were used in modifying the items of the quetionnaire. Similarly, to present the results of the pilot test, the data was analysed using PLS-SEM 2.0 and the findings confirmed the validity and reliability of the instruments adapted for the study. Theoretically, the paper established a new insight on the role of government on the relationship between the determinants and SMEs performance. The study has practical implication for government, policy makers, regulators, SMEs owner-managers and other stakeholders to recognize government support as it affects SMEs performance. The study further adds to the frontier of knowledge on the importance of GSPs in strengthening the relationship between the variables and SMEs performance.